2013
DOI: 10.2147/cmar.s38768
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal approach for the treatment of a large clival giant cell tumor complicated by an intraoperative internal carotid artery rupture

Abstract: Giant cell tumors (GCTs) are primary bone neoplasms that rarely involve the skull base. These lesions are usually locally aggressive and require complete removal, including the surrounding apparently healthy bone, to provide the best chance of cure. GCTs, as well as other lesions located in the clivus, can nowadays be treated by a minimally invasive fully endoscopic extended endonasal approach. This approach ensures a more direct route to the craniovertebral junction than other possible approaches (transfacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…Identification of the injury site may be a challenge given the constricted surgical space and the need to keep the endoscope clean to maintain adequate visualization. Multiple retrospective studies have recommended a 2‐surgeon approach because it may be beneficial to introduce an additional suction into the field, diverting blood from the endoscope and maintaining visualization . The most commonly reported ICA segment injured is the C4 (parasellar) segment; however, the C2 (petrous), C3 (paraclival), and C5 (paraclinoidal) segments have also been reported .…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the injury site may be a challenge given the constricted surgical space and the need to keep the endoscope clean to maintain adequate visualization. Multiple retrospective studies have recommended a 2‐surgeon approach because it may be beneficial to introduce an additional suction into the field, diverting blood from the endoscope and maintaining visualization . The most commonly reported ICA segment injured is the C4 (parasellar) segment; however, the C2 (petrous), C3 (paraclival), and C5 (paraclinoidal) segments have also been reported .…”
Section: Complicationsmentioning
confidence: 99%
“…Once the injury site has been identified, initial control of the hemorrhage is attempted with packing and compression . Packing materials reported for initial hemostatic control include gauze, oxidized cellulose ([Surgicel™ (Ethicon, Inc.; Somerville, NJ)], cottonoids/cotton strips, Surgifoam™ (Ethicon, Inc.; Somerville, NJ), and Merocel (Medtronic Inc., Minneapolis, MN) nasal packs with balloon tamponade . The most frequently reported packing material is gauze .…”
Section: Complicationsmentioning
confidence: 99%
“…Padhye et al and Iacoangeli et al reported the use of image guidance technology in one case each. The current literature remains controversial on the topic of intraoperative use of image guidance software and reduction in complications during EES .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Complete tumor removal and drilling of the surrounding healthy bone are preferable to expect a clinical cure and to reduce recurrence rate. 9 The recommended treatment of GCTs is functionpreserving surgery. 10 After complete resection, local control is achieved in 85% to 90% of all cases, but incomplete resection is frequently associated with tumor recurrence in up to 50% of the cases.…”
mentioning
confidence: 99%
“…10 Today, GCTs, as well as other lesions located in the sphenoid sinus and clivus, can be treated using an extended endoscopic endonasal approach (EEA) safely and effectively. 9 This approach gives a more direct route with better visualization to the craniovertebral junction than that of other possible approaches.…”
mentioning
confidence: 99%